A Deixis Analysis of Joe Biden’s Farewell Address to The Nation - Putri Angelina Gultom; Pius Eden Enjer Lombu; Anes Janie Stella Barus; Azra Asya Handoko (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2026)
This study aims to identify types of deixis and analyse their pragmatic functions in Joe Biden's farewell speech to the nation, delivered at the White House. Based on Stephen C. Levinson's (1983) theoretical framework, this descriptive qualitative study uses documentation techniques by analysing speech transcripts obtained from the official ABC News channel. The analysis found a total of 330 deixis expressions classified into five types: Deixis Persona, Deixis Discourse, Deixis Place, Deixis Time, and Deixis Social. The findings show that Deixis Persona is the most dominant type (60.3%), while the smallest is social deixis (3.9%). Discourse deixis (16.6%), Place deixis (10.3%), and Time deixis (9.3%). This study suggested that deixis was a powerful pragmatic method for engaging the audience, asserting authority, and shaping speaker identity in a political environment.